Genotype and phenotype correlation of breast cancer in young Kazakh women (Eurasian Journal of Ecology, 2022)
Breast cancer occupies a leading position in incidence and mortality from cancer among women worldwide and in Kazakhstan. Currently, modern genotyping methods are widely used for more accurate diagnosis and successful treatment of the disease. In this study, we analyzed the contribution of genetic variants of the BRCA2 gene to the pathogenesis and clinical heterogeneity of breast cancer among young ethnic Kazakh women under 40 years of age. 200 patients were examined. Using next-generation sequencing (NGS) and subsequent bioinformatic analysis, rare pathogenic variants were found in patients with breast cancer. All pathogenic variants met in the heterozygous state. 12 pathogenic variants in the BRCA2 gene were identified in 22 patients, among which were nonsense, frameshift indels, and inframe deletions. An analysis of the association between the mutational status and the disease's clinical features showed a relationship between the manifestation of a number of clinical and morphological features and the presence of pathogenic mutations in the BRCA2 gene in patients. Further research in the field of breast cancer genetics will contribute to obtaining a more accurate picture of the interaction of genotype and phenotype in this disease.Key words: breast cancer, next-generation sequencing, pathogenic mutations, BRCA2.